1977
DOI: 10.1111/j.1365-2125.1977.tb00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clofibrate on glucose tolerance in maturity onset diabetes.

Abstract: 1 Fourteen maturity onset diabetics showed improvement of glucose tolerance while on treatment with clofibrate. Fasting blood glucose levels were reduced by 20% after treatment for 14 and 28 days. 2 The effect was found to be independent of concurrent treatment with oral hypoglycaemic drugs. 3 Plasma insulin levels were also lower during clofibrate treatment. 4 Clofibrate may prove to be a useful adjunct to the treatment of maturity onset diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Skeletal muscle has been suggested to be the predominant site contributing to basal metabolic rate and thermogenesis in humans. 22 Our strategy to treat obesity entails enhancing thermogenesis in skeletal muscle, potentially by the up-regulation of UCP gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle has been suggested to be the predominant site contributing to basal metabolic rate and thermogenesis in humans. 22 Our strategy to treat obesity entails enhancing thermogenesis in skeletal muscle, potentially by the up-regulation of UCP gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported by several investigators that treatment with clofibrate improves glucose tolerance (1)(2)(3)(4), but other investigators reported that clofibrate did not have any effect on glucose tolerance (5,6). However, except for the study on insulin-dependent diabetic (IDDM) subjects re-…”
mentioning
confidence: 94%
“…In 22 diabetic patients, 11 of whom being insulin-dependent, clofibrate induced a significant reduction in glycosuria (Csogor & Bornemisza, 1977). In 14 maturity-onset diabetics, clofibrate significantly reduced fasting blood glucose (Barnett, Craig, Robinson & Rogers, 1977) and in 12 ketosis-prone insulin-dependent diabetics, Schade, Eaton, George, Conway, Kaminsky & Sivinski (1978) reported that clofibrate treatment resulted in a significant reduction in the concentrations of plasma glucose, ketone bodies and free fatty acids.…”
Section: Discussionmentioning
confidence: 99%